2022
DOI: 10.1002/tcr.202200123
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Two‐Dimensional Materials for Li/Na‐Ion Battery Anode Applications

Abstract: Two‐dimensional (2D) nanostructure is currently the subject in the fields of new energy storage and devices. During the past years, a broad range of 2D materials represented by graphene have been developed and endow with excellent electrochemical properties. Among them, elemental 2D materials (Xenes) are an emerged material family for Li/Na‐ion battery (LIB/SIB) anodes. Compared with other 2D materials and bulk materials, Xenes may exhibit some great superiorities for Li/Na storage, including excellent conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 166 publications
0
7
0
Order By: Relevance
“…Other materials for LPBs mainly include copper vanadate (CuV 2 O 6 ) [ 12 ], silver vanadium oxide (Ag 2 V 4 O 11 ) [ 13 ], aluminum fluoride (Li/AlF 3 ) [ 2 ], and manganese dioxide (Li/MnO 2 ) [ 14 ] with layered structures. However, unfortunately, the multistep reductions that occur during the insertion/intercalation of lithium in these materials results in their low specific capacity [ 15 ]. Two-dimensional metal chalcogenides (2DMCs) with carbon are a well-studied system for lithium batteries [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other materials for LPBs mainly include copper vanadate (CuV 2 O 6 ) [ 12 ], silver vanadium oxide (Ag 2 V 4 O 11 ) [ 13 ], aluminum fluoride (Li/AlF 3 ) [ 2 ], and manganese dioxide (Li/MnO 2 ) [ 14 ] with layered structures. However, unfortunately, the multistep reductions that occur during the insertion/intercalation of lithium in these materials results in their low specific capacity [ 15 ]. Two-dimensional metal chalcogenides (2DMCs) with carbon are a well-studied system for lithium batteries [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that Mo doping and Se vacancies can regulate the electronic structure of Co 9 Se 8 @NiSe/NF step by step, which optimized the adsorption energy for oxygenated intermediates and thus promoted the catalytic activity. 48–52…”
Section: Resultsmentioning
confidence: 99%
“…29 Furthermore, the inclusion of conductive carbon materials such as carbon black, graphene, and carbon nanotubes has proven effective in enhancing operational efficiency. 30–33 Shadike synthesized CoS 2 /Multi-Carbon Nanotube (MWCNT) composites by incorporating carbon-based materials, resulting in enhanced sodium storage properties with a capacity of 568 mAh g −11 . 34 Using polyaniline as a surface coating for Co 4 S 3 nanotubes, Zhou achieved notable improvements in electrode conductivity and cycling stability.…”
Section: Introductionmentioning
confidence: 99%